Teaching reading comprehension to weak readers: An investigation on teachers' beliefs on the use of chunking as a reading comprehension strategy / Sarawatihaslinda Abdul Wahid - Abdul Wahid, Sarawatihaslinda (2005)
The ability to read and understand what is read is an essential aspect in learning, as it plays an integrative significant role in disseminating information through other skills of speaking, listening and writing. However, the issue of students' weak performance in English today is said to be caused by their inability to understand their reading. Due to that, improvement in the areas of teaching strategies is often debated. This research is an effort to investigate the teachers' perceptions and readiness to adapt a reading strategy named chunking. A sample group which consisted of 17 English teachers of Sek. Men. Kebangsaan Seksyen 16, Shah Alam was asked to answer a survey questionnaire and attend a workshop on chunking. Using a quantitative approach, the data were analysed to look into the insights of the strengths and weaknesses of the teachers' reading strategies on the students, their hopes, beliefs and willingness to adapt to changes in teaching pedagogy such as chunking. An informal interview was conducted to get further elaboration or information on certain issues pertaining to the survey questions. The findings showed that the students' weak performance in English is due to the weak teaching strategies practiced by the teachers. In teaching reading, most of the activities were teacher-centred approaches. This kind of dominant role played by the teachers affected the students to be over-dependent learners. As a result, they failed to perform satisfactorily in their academic achievement. Nevertheless, the teachers show positive beliefs towards chunking strategies which offered better student-centred learning and they are willing to adapt the strategies to their weak learners. The research also concludes by highlighting factors that influenced teachers' performance and discussing the ways to improve teachers' pedagogical skills.